Pool of Processors on the Web - Lopes, Denivaldo; Saavedra, Osvaldo; Abdelouahab, Zair (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
This paper presents ESOW (An Environment of Shared Object for Web) to support parallel and distributed programming on Web or Intranet. The environment allows that computers with low computational resources take advantage of idle computers present on the Web. ESOW is a Pool of available computers to share two basic resources: processor and memory. The main entities in this environment are passive and active objects. Passive objects are lists, stacks and queues which store others objects defined by users. While active objects are processes. The proposed environment implements load balancing and tolerance to fault. Some tests show the ESOW power.